Hyperbaric Oxygen Therapy of an Adolescent Stem Cell Transplantation Recipient with Hemorrhagic Cystitis and BK Virus - David López; Abdullah Alismail; Laren D. Tan (Case Reports in Pulmonology)
Hyperbaric oxygen therapy (HBOT) continues to show effectiveness in the treatment of several diseases and benefits such as fibroblast proliferation, capillary angiogenesis, and decreasing edema, especially in hemorrhagic cystitis (HC). We report a case of a 15-year-old male with chronic myelogenous leukemia status posthaploidentical stem cell transport with BK virus in the United States to be treated by HBOT. The patient received a total of 30 HBOT treatments for 90 minutes at 2 ATA. After HBOT treatments, patient showed signs of improvements such as cessation of hemorrhage cystitis. The findings of this case support and shows that there is growing evidence for the use of HBOT as adjunctive therapy for patients with BK virus associated with HC after stem cell transplantation.